Challenges and impacts of religious endowments on global economics and finance - Saiti, Buerhan, 1983-; Sarea, Adel, 1979- (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book explores the challenges and impacts of religious endowments on global finance and economics"--